Dilema Eksistensi di Era Digital: Analisis Fenomena Flexing di Media Sosial dalam Perspektif Psikologi Sosial dan Islam - S. Manhatus Sania (Jurnal Budi Pekerti Agama Islam, 2026)
The phenomenon of flexing on social media has become increasingly visible in the digital era. This behavior is characterized by individuals displaying wealth, achievements, and certain lifestyles in order to gain attention and social recognition. This study aims to analyze the phenomenon of flexing from the perspectives of social psychology and Islam, as well as to examine its impact on the psychological and spiritual conditions of Muslim society. The research employs a qualitative method through a literature study by utilizing various sources, including the Qur’an, interpretations of the Qur’an, social psychology theories, and relevant scientific journals. The collected data were analyzed using thematic content analysis. The findings indicate that flexing behavior is closely related to individuals’ needs for recognition, self-existence, and self-actualization within society. From an Islamic perspective, such behavior may be acceptable if it reflects gratitude and provides positive motivation without involving arrogance or showing off. However, excessive flexing has the potential to encourage consumptive behavior, social anxiety, fear of missing out, and the decline of moral and spiritual values. Therefore, wiser use of social media is necessary through strengthening digital literacy and instilling the values of simplicity and humility in everyday life so that social media can be utilized in a healthier and more responsible manner.